Analysis of Factors Related to the Incidence of Dermatitis in Adolescents in Namo Buaya Village Sultan Daulat District - Azimi Sambo; Tahara Dilla Santi; Riza Septiani (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Contact dermatitis is a common inflammatory condition of the skin due to exposure to allergens or irritants that trigger an immune response and inflammation of the skin and mucous membranes. Objective: This study aims to determine the factors associated with contact dermatitis in Namo Buaya Village Sultan Daulat District, Subulussalam City in 2024. Based on data from the Sultan Daulat Health Center in January Until May 2024, 1 08 adolescent patients were recorded diagnosed with contact dermatitis. Method: This study was an analytical observational study with a case control design. The sample of this research was 194 respondents were divided into 97 case groups and 97 control groups (1:1 ratio). Data collection was conducted on June 3-8, 2024 using a questionnaire and analyzed using the Chi-Square test. Results: Univariate results showed that (50%) of respondents suffered from dermatitis, (57.2%) had unqualified water, (50.5%) were exposed to chemicals, (55.7%) were female, (52.6%) had secondary education, (51%) were unemployed and (56.2%) had poor personal hygiene. Bivariate results showed that there was a relationship between water characteristics (p -value = 0.006, OR = 0.444), chemical exposure (p - value = 0.022, OR = 0.514), gender (p -value = 0.021, OR = 0.509), parental education (p -value = 0.028, OR = 0.570), occupation (p - value = 0.031, OR = 0.536), and personal hygiene (p -value = 0.002, OR = 0.409) with dermatitis. Conclusion: This study concludes that all variables have a relationship with dermatitis in Namo Buaya Village, Sultan Daulat District, Subulussalam City in 2024. It is hoped that health workers will provide education about dermatitis, water characteristics, exposure to chemicals, gender, education, occupation, personal hygiene, and the community maintains personal hygiene to prevent the disease.